2022
DOI: 10.3389/fnut.2022.996932
|View full text |Cite
|
Sign up to set email alerts
|

A new selenium source from Se-enriched Cardamine violifolia improves growth performance, anti-oxidative capacity and meat quality in broilers

Abstract: BackgroundCardamine violifolia (Cv) is a kind of selenium-enriched plant which contains high levels of organic selenium (Se) such as selenocysteine and methylselenocysteine. This study was conducted to investigate the effects of this new source of Se on the growth performance, anti-oxidative capacity and meat quality in broilers compared with other frequently-used Se sources.MethodsA total of 240 broilers were allotted into 4 treatments: (1) Control group (Se free diets, CON); (2) Sodium selenite group (0.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Our study showed that dietary SeCe supplementation alleviated transport-stress-induced meat quality reduction of breast and thigh muscle in broilers. In agreement with our results, other studies have reported the better effect of SeCe on meat quality of broilers compared with Na 2 SeO 3 [ 12 , 13 ]. The reason may be that Se increases oxidation resistance and prevents muscle protein being oxidized [ 39 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that dietary SeCe supplementation alleviated transport-stress-induced meat quality reduction of breast and thigh muscle in broilers. In agreement with our results, other studies have reported the better effect of SeCe on meat quality of broilers compared with Na 2 SeO 3 [ 12 , 13 ]. The reason may be that Se increases oxidation resistance and prevents muscle protein being oxidized [ 39 ].…”
Section: Resultssupporting
confidence: 93%
“…A previous study demonstrated that organic Se had higher anti-oxidative capacity compared with inorganic Se [ 34 ]. SeCe is a hyperaccumulating plant newly discovered in China and the Se mainly exists in SeCe in the organic form of SeCys 2 and MeSeCys [ 12 ]. The better effect of dietary SeCe supplementation on anti-oxidative capacity of broilers under transport stress may be due to the form of organic Se occurring in SeCe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supplemental Selenium Yeast in organic trace minerals can support the highest growth of broiler chicks (Arnaut et al, 2021;Wang et al, 2021;Bakhshalinejad et al, 2018). In addition, Xu et al (2022) reported that a new source of selenium-enriched plants with high levels of organic Se is an acceptable Se source for broilers. In contrast, the average growth performance of broilers supplemented with organic selenium is lower than those supplemented with inorganic selenium.…”
Section: Discussion the Performance Of Broilersmentioning
confidence: 99%
“…The Se concentration in the leaves of Se-enriched Cardamine violifolia (SEC) is greater than 700 mg/kg (dry weight), with over 85% of the complete Se deposited in the form of organic Se, such as selenocysteine and methylselenocysteine [ 17 ]. Our previous study indicated that dietary SEC supplementation enhanced the growth performance and antioxidant capacity of broilers [ 18 ]. Few studies have been performed to estimate the effects of SEC supplementation in a hen’s diet on egg quality during egg storage.…”
Section: Introductionmentioning
confidence: 99%